PUBLIC POLICIES, PRIMERS FOR CONFRONTING CHILD SEXUAL VIOLENCE AND VOCATIONAL TRAINING: SOME POSSIBILITIES - Lucca, Roger de; Candido Carneiro, Rita de Kassia [UNESP]; Vicente, Aparecido Renan; Castro Leao, Andreza Marques de (Fundacao Univ Tocantins, 2021)
This article analyzes issues related to guaranteeing children's rights, focusing on the emergence of the Child and Adolescent Statute (ECA), its changes and innovations aimed at protecting boys and girls. As of this law, security measures were rethought and the fight against any type of violence against this public was put on the agenda. Considering this,we aim in this study to include awareness actions aimed at protecting children, through the production of booklets.Therefore, qualitative research was used, focusing on the selection of materials concerned with the eradication of this phenomenon. As a result of the search, booklets produced between 1998 and 2018, initiatives of Brazilian entities and states, were found, representing the proliferation of the idea of protecting children and adolescents. In general, they conceptualize abuse, bringing forms of notification, as well as prevention tips. After discussing this type of material,we highlighted the importance of training for professionals involved with the protection network. Therefore, it is necessary that this theme is part of the curriculum of universities and also in the agendas for training professionals in these areas, so that they can help children in identifying and referring cases of child sexual violence.
Keywords: CAS; Primers; Professional Training; Prevention Against Child Sexual Violence